2014
DOI: 10.1007/s00330-014-3108-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing liver function by liver enhancement during the hepatobiliary phase with Gd-EOB-DTPA-enhanced MRI at 3 Tesla

Abstract: Hepatic uptake of Gd-EOB-DTPA is strongly affected by liver function. Relative enhancement during HBP in GD-EOB-DTPA MRI correlates with the MELD score. Assessment of relative enhancement may help improve treatment in routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 34 publications
1
92
1
Order By: Relevance
“…The recent report by Verloh et al [15] also focused on the usefulness of Gd-EOB-DTPAenhanced MRI to determine the hepatic functional reserve and the results are quite similar as ours; the uptake of Gd-EOB-DTPA in hepatocysts is strongly affected by liver function. In our study, we added on information about the interobserver reliability of the percentage enhancement as well, which shows substantial agreement.…”
Section: Discussionsupporting
confidence: 85%
“…The recent report by Verloh et al [15] also focused on the usefulness of Gd-EOB-DTPAenhanced MRI to determine the hepatic functional reserve and the results are quite similar as ours; the uptake of Gd-EOB-DTPA in hepatocysts is strongly affected by liver function. In our study, we added on information about the interobserver reliability of the percentage enhancement as well, which shows substantial agreement.…”
Section: Discussionsupporting
confidence: 85%
“…After administration, both ICG and Gd-EOB-DTPA uptake into functional hepatocytes are dependent on the same transport mechanisms that are mediated by the organic anion transporters OATP1B1/B3 [7]. The temporary accumulation of Gd-EOB-DTPA in the liver leads to an enhancement of normal liver parenchyma, which may be used as an indicator for the quantitative evaluation of liver function [8][9][10][11]. Other studies have shown that estimations of total liver function using parenchymal enhancement of the liver may be improved by taking into account the respective liver volume (LV) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) and magnetic resonance imaging (MRI) using gadoxetic acid (Gd-EOB-DTPA) have recently shown promise for the evaluation of segmental liver functional reserve [6][7][8][9][10][11]. DWI is based on the random Brownian motion of water molecules within the voxel.…”
Section: Introductionmentioning
confidence: 99%